Letter (copy) : Ricardo Zabalza - Citrine, Walter, 1887-1983
013-0118-001 International. WMC/WJB/DT/427. 12th January, 1940. Mr. Orencio Labrador, c/o, Mrs. Peech, Fugle-Frith, Cudham, KENT. Dear Sir, RICARDO ZABALZA. I am in receipt of your letter of the 2nd of January, and I am very sorry to have the news about Ricardo Zabalza, former Secretary of the Land Workers' Union. I immediately took up the case with the Authorities here and have earnestly requested them to consider whether in the present circumstances, anything could be done to alleviate the position of Zabalza, and to induce the Spanish Government to rescind the sentence that has bee passed on him. Yours faithfully, General Secretary. 292/946/13/118